<h3>
Answer: y = x+1</h3>
===================================================
Explanation:
f(x) = x^3 - 2x + 3
f ' (x) = 3x^2 - 2 ..... apply the power rule
f ' (1) = 3(1)^2 - 2 ... plug in x coordinate of given point
f ' (1) = 1
If x = 1 is plugged into the derivative function, then we get the output 1. This means the slope of the tangent line at (1,2) is m = 1. It's just a coincidence that the x input value is the same as the slope m value.
Now apply point slope form to find the equation of the tangent line
y - y1 = m(x - x1)
y - 2 = 1(x - 1)
y - 2 = x - 1
y = x - 1 + 2
y = x + 1 is the equation of the tangent line.
The graph is shown below. I used GeoGebra to make the graph.
Answer:
<h3> The first: The easiest to solve for is x in the first equation.</h3>
Step-by-step explanation:
To get x from first equation you just need to subtract 4y from both sides.
The rest of variables needs two operations to get variable - subtracting and then dividing.
Answer:
6 + (3xd)
Step-by-step explanation:
Answer:
<u>Step-by-step explanation:</u>
Note the following identities: tan² x = sec²x - 1
tan² x + sec x = 1
(sec² x -1) + sec x = 1
sec² x + sec x - 2 = 0
(sec x + 2)(sec x - 1) = 0
sec x + 2 = 0 sec x - 1 = 0
sec x = -2 sec x = 1